(untitled) - Odendaal, Caitlin Paige

Chronic stress elicits sex-specific mitochondrial respiratory functional changes in the rat heart (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.